Uma proposta de sequência didática envolvendo conceitos relacionados ao uso da energia fotovoltaica para o ensino fundamental - Mattos, Romério Cossi (2023)
This work is research of the pedagogical intervention type in which the formation of basic concepts of electricity related to classical electrodynamics was investigated, from the application of a systematized didactic sequence in the three pedagogical moments with a CTS approach with the use of photovoltaic energy in elementary education. The didactic sequence consists of 12 (twelve) classes and was applied in two classes of the eighth year of elementary school, with a total of 71 students, in a school of the state education network, in the municipality of Cariacica/ES. The teaching sequence was developed in the three pedagogical moments. The specifics of each one of them are the following: moment of the initial problematization, where questions were presented that relate the basic concepts of electricity to the situations that the students witness in their daily lives; moment of knowledge organization, in which the basic concepts of electricity were systematically studied under the teacher's mediation, through dialogued expository classes and use of instructional materials, such as: experiments and computer simulation PhET (Physics Education Technology Project), made available free on the internet by the University of Colorado, which virtually simulates assemblies of electrical circuits, a demonstrative simulation of the Vascak simulator and moment of the application of knowledge, where questions were presented to approach the concepts of electricity used in daily life, dialoguing with the STS perspective. The analytical movement emphasized the appropriation process of scientific terms related to electricity, the identification of evidence of the construction of concepts related to electrical magnitudes and the practical application of this scientific and technological knowledge to different social contexts. The analytical results showed evidence that the students approached the scientifically accepted concepts and that, therefore, the educational activity developed in three pedagogical moments with the STS approach using photovoltaic energy, in the way it was xvi conducted, is a valid pedagogical alternative and suitable for teaching basic concepts of electricity referring to classical electrodynamics, from a socio-scientific perspective.